3D Honeycomb‐Like Structured Graphene and Its High Efficiency as a Counter‐Electrode Catalyst for Dye‐Sensitized Solar Cells1. Issue 35 (29th July 2013) - Wang, Hui; Sun, Kai; Tao, Franklin; Stacchiola, Dario J.; Hu, Yun Hang
<x xml:space="preserve">Abstract</x> A useful Li: A simple reaction between Li2O and CO, gives a new type of three‐dimensional graphene sheets—honeycomb‐structured graphene. A dye‐sensitized solar cell (DSSC) with the new graphene counter electrode has an energy conversion efficiency as high as 7.8 %, which is comparable to that of DSSCs with an expensive Pt counter electrode.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>